Euro area money demand and international portfolio allocation: a contribution to assessing risks to price stability - Roberto A. De Santis; Carlo A. Favero; Barbara Roffia (European Central Bank (ECB), 2008)
The long-run relationship between money and prices in the euro area embedded in traditional money demand models with income and interest rates broke down after 2001. We develop a money demand model where investors hold a diversified portfolio with money, domestic and foreign stocks and long-term bonds in which, in addition to the classical wealth effect, also a size and an international portfolio allocation effects arise. The estimated model identifies three cointegrating vectors stable over the sample 1980-2007: a long-run money demand, which depends on income and all risky assets' returns, and two equilibria for the euro area and the US financial markets. Steady state equilibrium of nominal M3 growth is estimated to be about 7% in 2007 with large standard errors mainly due to uncertainty in asset prices. The gap between actual euro area M3 growth and model-based fitted or predicted values helps forecast euro area inflation.
Keywords: E41; E44; E52; G11; G15; 330; Euro area money demand; Inflation forecasts; monetary policy; portfolio allocation; Geldnachfrage; Inflationserwartung; Geldpolitik; Portfolio-Management; Anlageverhalten; Eurozone; EU-Staaten